2012
DOI: 10.15562/ijbs.v3i1.64
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intensive Insulin Therapy on Superoxide Dismutase (Sod), Tumor Necrosis Factor-? (Tnf-?), and Interleukin-6 (Il-6) on Hyperglycemia in Critically Ill Patients

Abstract: Hyperglycemia and insulin resistance are common in critically ill patientsin the ICU, although they have not previously had diabetes. It has been reportedthat pronounced hyperglycemia may lead to complications in such patients, andcause the reactive oxygen species (ROS) production, although controlled trial dataare still lacking. The current debatable issue, focusing on whether the intensiveinsulin therapy, aimed at normalizing blood glucose, may improvepatients’prognosis. Then, the debate is mainly about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…In this study, giving diabetic rats EEPML reduced the average IL-6 level significantly (p=0.017). This result is similar to a study that showed intensive insulin therapy in critically ill people with high blood sugar lowered their IL-6 levels (p=0.023) ( 12 ). Metformin can also lower IL-6 in people with T2DM while raising the levels of IL-10 ( 13 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, giving diabetic rats EEPML reduced the average IL-6 level significantly (p=0.017). This result is similar to a study that showed intensive insulin therapy in critically ill people with high blood sugar lowered their IL-6 levels (p=0.023) ( 12 ). Metformin can also lower IL-6 in people with T2DM while raising the levels of IL-10 ( 13 ).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, giving EEPML to diabetic rats lowered the mean serum TNF-α levels, but the drop was not statistically significant (p=0.266). This result is similar to a study that showed intensive insulin therapy in critically ill people with high blood sugar could not lower their TNF-α levels (p=0.078) ( 12 ). The effects of herbal plants that contain flavonoids potentially decreased TNF-α expression in pancreatic tissue and repaired that damaged pancreatic tissue, and decreased the severity of insulitis (p<0.05) ( 19 ).…”
Section: Discussionsupporting
confidence: 90%